EMPLOYEE WELFARE PRACTICE IN BATTERY INDUSTRY: AN EMPRICAL STUDY - Dr Panthula Sree Sai Pavan , T L Eswar Kumar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Welfare practice includes various facilities, services and conveniences facilitated to the employees for boosting their lifestyle. It comprises both statutory and non-statutory provisions laid by the various industry bodies. The aims of this paper to explore various employee welfare schemes adopted by battery industries of India. It includes social, economic, moral, cultural, ethical and cognitive ability of the employees in order to nurture them as a good citizen. This paper is based on secondary data collected from various published and unpublished data collected from various sources. Generally welfare schemes are depends upon the interests of the employer towards their employees’ wellbeing and it also covers social security. The result of this study concludes that the very logic behind providing the welfare schemes is to create efficient, healthy, loyal and satisfied labor force for the organization. The purpose of providing such facilities is to make their work life better and also to raise their standard of living.